Case Report: von Hippel-Lindau (VHL) disease: a young female presenting with multiple organ tumors - Li, Jingyuan; Ti, Yun; Yang, Xiao; Yan, Keqiang; Chen, Tongshuai; Guo, Tao; Hu, Qin; Zhang, Cheng; Bu, Peili (Frontiers in Genetics, 2025)
This report presents a case involving a young female patient diagnosed with von Hippel-Lindau (VHL) syndrome. The patient developed multiple sequential tumors, including spinal cord hemangioblastoma, multiple pancreatic cysts, and pheochromocytoma. Whole-genome sequencing identified a deletion mutation in exon 3 of the VHL gene, challenging the previous understanding that VHL deletion mutations are highly prevalent in hemangioblastoma and renal cell carcinoma but uncommon in pheochromocytoma. This case underscores the importance of considering hereditary genetic syndromes in patients presenting with hypertension and multi-system tumor involvement. Comprehensive evaluation, standardized familial screening, and genetic testing play a crucial role in guiding treatment decisions for affected individuals.